Art, Science, and Craft of Great Landscape Photography, 2nd Edition - Randall, Glenn (Rocky Nook, 2020)
The Art, Science, and Craft of Great Landscape Photography, 2nd Edition teaches photographers how to convert their visual peak experiences--moments of extraordinary natural beauty that evoke a sense of wonder and awe--into stunning images that elicit the same awestruck emotion in their viewers. Author Glenn Randall is an experienced wilderness photographer, and whether you want to venture into the mountains for once-in-a-lifetime shots of raw nature, or simply hone your landscape photography skills from the safety of your back deck, Randall explains the art, science and craft behind creating stunning landscape photographs. This fully updated edition of the best-selling first edition includes nearly all new imagery throughout the book, as well as a new first chapter, "Photographic Essentials," to help beginners to landscape photography get up to speed quickly. Additionally, this second edition takes into account how Randall's techniques have changed and evolved since the first edition published--from photographic practices to how he uses smart phones and apps as important and powerful tools for landscape photography. After discussing photographic essentials, Randall focuses on the art of landscape photography. He describes his three-step process for composing a photograph and shows how good composition is an organic process that begins with rules but ultimately transcends them. Randall then explores the science behind successful landscape photographs, which requires understanding key concepts from geography, optics, vision, and psychology. These concepts include: " How the position of the sun at sunrise and sunset varies throughout the year. This will help you plan when and where to shoot." Using optics to predict where rainbows will appear, how polarizers will interact with reflections, and where to find spectacular light." How to use topographic maps and computerized mapping tools to help you find promising shooting locations in the wilderness." Calculating exposures, achieving correct exposure in high-contrast lighting situations, and the best digital darkroom techniques. With some practice and by applying the techniques that Randall teaches you, you will soon be ready to master the finer nuances of creating magnificent landscape photographs. TABLE OF CONTENTS Introduction Chapter 1: Photographic Essentials Chapter 2: Landscape Photography Looks So Easy Chapter 3: In Search of Extraordinary Landscapes Chapter 4: Visualization Chapter 5: ...